Observational study of adherence to a traditional Mediterranean diet, sociocultural characteristics and cardiovascular disease risk factors of older Greek Australians from MEDiterranean ISlands (MEDIS‐Australia Study): Protocol and rationale. Issue 1 (24th July 2017) - Thodis, Antonia; Itsiopoulos, Catherine; Kouris‐Blazos, Antigone; Brazionis, Laima; Tyrovolas, Stefanos; Polychronopoulos, Evangelos; Panagiotakos, Demosthenes B.
Abstract : Aim: To describe the study protocol of the MEDiterranean ISlands‐Australia (MEDIS‐Australia) Study modelled on the MEDIS Study conducted in Greece. The present study aims to explore adherence to the traditional Mediterranean diet pattern, determine enablers and barriers to adherence, explore the definition of Greek cuisine, and associations between adherence to the diet pattern and risk factors for cardiovascular disease (CVD) and metabolic syndrome in older Greek Australians originally from Greek islands and Cyprus. Now long‐term immigrants, with at least 50 years in Australia, characteristics and risk factor profiles of older Greek islander‐born Australians will be compared and contrasted to their counterparts living on Greek islands to evaluate the influence of migration on adherence. Methods: The present study is an observational study of cross‐sectional design using a modified lifestyle and semi‐quantitative food frequency questionnaire to capture sociodemographic, health, psychosocial and dietary characteristics, including cuisine, of 150 older Greek islander‐born Australians. Anthropometric measures and medical history will be collected. Participants will be aged over 65 years, live independently, are originally from a Greek island and are free from CVD. Results: Data collection is underway. Conclusions: Characteristics and behaviours associated with adherence, if identified, could be evaluated in future studies. For example, exploration of enablers or barriers to adherence to a Mediterranean dietary pattern in an Australian population.